ChemInform Abstract: Platform for Ring‐Fluorinated Benzoheterole Derivatives: Palladium‐Catalyzed Regioselective 1, 1‐Difluoroallylation and Heck Cyclization. Issue 22 (12th May 2016) - Fujita, Takeshi; Sugiyama, Kazuki; Sanada, Shohei; Ichitsuka, Tomohiro; Ichikawa, Junji
Abstract: Conditions for the title reaction between 2‐bromophenols or 2‐bromo‐N‐sulfonylanilines with 3‐bromo‐3, 3‐difluoropropene for the efficient formation of ring‐difluorinated dihydrobenzofuran or indoline derivatives, respectively, are elaborated.